Kecenderungan agresivitas pada suporter Persebaya: Bagaimanakah peranan persepsi kekalahan dan fanatisme? - Adilla, Maulfi Bianda; Amanda Pasca Rini; Sahat Saragih (INNER: Journal of Psychological Research, 2023)
This study aims to determine the relationship between perceptions of defeat and bigotry with aggressive tendencies. This study has three hypotheses, which contain: 1) there is a positive relationship between perceptions of defeat and bigotry with aggressive tendencies; 2) there is a positive relationship between the perception of defeat and the tendency to be aggressive; 3) there is a positive relationship between fanaticism and aggressive tendencies. Data collection was carried out for six days by distributing questionnaires on the scale of perceptions of defeat, fanaticism, and aggressive tendencies online to Persebaya supporters in Surabaya as many as 207 respondents. Data analysis used was multiple regression analysis with the help of SPSS 26. The results of this study indicate 1) There is a positive relationship between perceptions of defeat and bigotry with aggressive tendencies; 2) There is a positive relationship between perceptions of defeat and aggressive tendencies. This means that the higher the perception of defeat, the higher the aggressive tendency; 3) There is no positive relationship between fanaticism and aggressive tendencies. This means that high or low fanaticism does not affect the high or low aggressive tendencies. Therefore, the first and second hypotheses in this study are accepted, while the third hypothesis is not accepted. Keywords: : Perception of Defeat; Fanaticism; Aggressive Tendencies; Persebaya supporters